2016
DOI: 10.1080/19336950.2016.1185579
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 is functionally co-expressed with TRPV1 in cardiac muscle: Co-localization at z-discs, costameres and intercalated discs

Abstract: Transient receptor potential channels of the ankyrin subtype-1 (TRPA1) and vanilloid subtype-1 (TRPV1) are structurally related, non-selective cation channels that show a high permeability to calcium. Previous studies indicate that TRP channels play a prominent role in the regulation of cardiovascular dynamics and homeostasis, but also contribute to the pathophysiology of many diseases and disorders within the cardiovascular system. However, no studies to date have identified the functional expression and/or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 56 publications
0
61
1
Order By: Relevance
“…If cardiac protection was neuron mediated, the ability for ischaemic preconditioning to reduce myocardial infarct size should not be abolished in an isolated heart model. We and others recently identified that TRPV1 is present and functional within the cardiac myocyte (Andrei et al, 2016;Hurt et al, 2016). TRPV1 also modulates myocardial ischaemiareperfusion injury through the regulation of mitochondrial membrane potential (Hurt et al, 2016).…”
Section: Figurementioning
confidence: 84%
“…If cardiac protection was neuron mediated, the ability for ischaemic preconditioning to reduce myocardial infarct size should not be abolished in an isolated heart model. We and others recently identified that TRPV1 is present and functional within the cardiac myocyte (Andrei et al, 2016;Hurt et al, 2016). TRPV1 also modulates myocardial ischaemiareperfusion injury through the regulation of mitochondrial membrane potential (Hurt et al, 2016).…”
Section: Figurementioning
confidence: 84%
“…8 To our knowledge, the current study is the first to thoroughly characterize the effects of TRPA1 stimulation on [Ca 2C ] i and contractile function in electrically-stimulated adult mouse CMs. The major finding of the current study is that TRPA1 agonist, AITC, stimulates dose-dependent increases in peak [Ca ] i and contractile function were qualitatively and quantitatively similar to the classical CM responses observed following b-AR stimulation with ISO, we did not observe any increase in CM cAMP production or PKA activity following TRPA1 activation with AITC, and the PKA inhibitor peptide was without effect on AITC induced modifications in CM [Ca 2C ] i and contractile function.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] We recently reported for the first time the expression of TRPA1 at the protein level in cardiac muscle and it's co-localization with TRPV1 ion channels at the costamere, z-disk and intercalated discs in murine cardiomyocytes (CM). 8 However, the extent to which TRPA1 ion channel stimulation plays a role in the regulation and/or modulation of CM contractile function have not been previously reported. In the current study, we tested the hypothesis that stimulation of TRPA1 ion channels in electrically-stimulated mouse ventricular CMs results in increases in peak intracellular free Ca 2C concentration ([Ca 2C ] i ) and a concomitant increase in CM contractile function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established in sensory neurons [11, 13] and in other tissue types [36] that receptor activation with capsaicin (specific TRPV1 agonist) or allyl isothiocyanate (TRPA1 agonist) results in channel activation and a transient influx of Ca 2+ leading to an increase in intracellular free Ca 2+ concentration [Ca 2+ ] i . Although there is no evidence of propofol-induced TRPV1-mediated calcium-influx, we previously demonstrated that propofol induces a transient increase in [Ca 2+ ] i via a TRPA1-dependent pathway in sensory neurons [11].…”
Section: Discussionmentioning
confidence: 99%